O estágio supervisionado em retrospectiva: revisitando a educação inclusiva na escola - Labas, Kaline Oliveira (2024)
The aim of this study was to analyze the formative relationship between the supervised curricular internship and teaching practice in basic education, with a specific focus on inclusive education, at a school in the Municipal Education Network of Areial, a municipality in the state of Paraíba, Brazil. In the current context, the inclusion of students with disabilities represents a major challenge for the education system. Despite inclusive educational policies that prioritize the enrollment of students with disabilities and special needs, as well as investments in infrastructure, teaching materials, and pedagogy, one of the main barriers to access to learning and the development of teaching practices that meet the individual needs of students lies in teacher training.This research adopted a qualitative approach, using semi-structured interviews. The subjects of the study were basic education teachers who work with students with disabilities or special needs. The collected data were analyzed using content analysis, following the methodology proposed by Bardin (2009). The specific objective of the research was to analyze the influence of the supervised internship on the training of basic education teachers, with a focus on Inclusive Education, and to identify how the formative experiences during the internship contribute to the implementation of inclusive teaching strategies by teachers currently working in schools within the Municipal Education Network of Areial, Paraíba.The study was based on various theoretical references, including works by Pimenta (2019), Pavão (2019), Matoan (2007), Mendes (2018), Contreras (2002), and Basso (2019). The results indicated that, although inclusive educational policies have advanced, teachers faced significant difficulties during their supervised internships, especially due to the lack of support at the internship institutions.Another point identified was the importance of personal interest in the completion of the internship practices. This interest was a key factor in the teachers’ greater commitment to their initial training. Although the supervised internship has limitations, it was considered a relevant stage in the formation of teachers committed to Inclusive Education and to the development of students. As an Educational Product, an e-book titled "Inclusive Education: A Guide for Teacher Training" was created and made available to the research participants via email in PDF format. This material aimed to promote the recognition of the importance of teacher training and to support the development of inclusive teaching practices, based on the reflections and findings generated by the data analysis. The goal of the e-book is to offer guidance for training teachers who are committed to inclusive education and to the appreciation of diversity in the school environment.